Towards a shift of values in rail infrastructure project evaluation - Langdon, Mark (2021)
The rail industry, despite its iconic value and status as a key economic infrastructure, faces significant challenges today: An ageing, historically underinvested system has had to accommodate an unprecedented increase in demand with limited financial resources at its disposal. Now, following the Covid pandemic the same historically underinvested infrastructure has had to address the reality of an unprecedented reduction. In order to meet these polarised challenges, brought sharply into focus by its imminent restructuring (initiated by the recent White Paper) it needs more than ever, to harness the positive socio-economic impact of its interventions on its key resource: its human potential. In this work the author argues that the value of enhanced skill, knowledge and expertise derived from projects should be recognised and incorporated into more meaningful evaluations of project viability and sustainability. The argument draws on the notions of sustainability, the nature of the asset base and a more comprehensive whole life evaluation to inform and make this case. It has been supported through the use of surveys and interviews, within the context of case studies, in order to represent the nature of the relationship between participation in projects and the enhancement of expertise. The findings describe both a strong relationship (80% agreement and strong agreement) between project participation and expertise enhancement as well as providing indications of some of its key qualities. Adding support to the assertion that there is a necessary and contributory causal relationship between project participation and the enhancement of the expertise of the participants. The Interviews, based on grounded theory, also provide further insights through the identification and distillation of themes which emerge as integral to this process and are consistent with the concepts drawn out from the notion of a sustainable intervention in rail assets. Supported by these findings the author concludes that the value derived from harnessing the potential of its key resource in this way needs greater recognition and to be incorporated into a more comprehensive calibration of project value. A more comprehensive form of whole life evaluation, which made greater accommodation of externalities, while at the same time recognising that rather than being an external attribute of asset value, the enhancement of skill, knowledge and expertise is, in fact, intrinsic to it. A recognition requiring a significant shift of emphasis in the realm of project evaluation and governance in order to ensure its rightful place in the effective incorporation and deployment of asset value